Comparative analysis of synchronization algorithms based on PLL, RDFT and Kalman Filter - Pádua, M. S.; Deckmann, S. M.; Sperandio, G. S.; Marafão, F. P. [UNESP]; Colón, D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper discusses the main characteristics and presents a comparative analysis of three synchronization algorithms based respectively, on a Phase-Locked Loop, a Kalman Filter and a Discrete Fourier Transform. It will be described the single and three-phase models of the first two methods and the single-phase model of the third one. Details on how to modify the filtering properties or dynamic response of each algorithm will be discussed in terms of their design parameters. In order to compare the different algorithms, these parameters will be set for maximum filter capability. Then, the dynamic response, during input amplitude and frequency deviations will be observed, as well as during the initialization procedure. So, advantages and disadvantages of all considered algorithms will be discussed. ©2007 IEEE.
Keywords: Algorithms; Control theory; Discrete Fourier transforms; Dynamic response; Electronics industry; Fourier transforms; Frequency response; Industrial electronics; Kalman filters; Mathematical transformations; Phase locked loops; Technical presentations; Telecommunication; Wave filters; Comparative analysis; Design parameters.; Filtering properties; Frequency deviations; International symposium; Phase modeling; Phase-locked loop; Single-phase model; Synchronization algorithms; Parameter estimation